Subjective Well-Being of Indonesian Children: A Perspective of Material Well-Being [Kesejahteraan Subjektif Anak Indonesia: Sebuah Perspektif Kesejahteraan Materi] - Ihsana Sabriani Borualogo; Ferran Casas (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
This study aims to explain the subjective well-being of Indonesian children in terms of material well-being. Indonesia is still considered a developing country, and several studies reveal the correlation between economic status and subjective well-being of adults. However, only a very limited number of studies focus on Indonesian children’s material well-being from their own perspective. This study used data from the third wave of the Children’s Worlds survey conducted in Indonesia. The sample (N = 14,576; 49.35% boys; 50.65% girls) was composed of children aged 10 years and 12 years. Subjective well-being (SWB) was measured using the Children’s Worlds Subjective Well-Being Scale (CW-SWBS) and a single-item Overall Life Satisfaction (OLS) scale. Material well-being was measured using family economic status, material deprivation, frequency of being worried about family’s money situation, and frequency of having enough food to eat each day. Data were analyzed using descriptive statistics. Cummins’ theory of subjective well-being (SWB) was used to explain the results. Results showed that children from families with high economic status who reported no material deprivation, never worrying about the family’s money, and always having enough food to eat each day displayed higher subjective well-being (SWB) mean scores on both subjective well-being (SWB) scales compared to children in families from middle and lower economic status. However, children from middle and lower economic status showed rather high subjective well-being (SWB) scores, suggesting that children are able to maintain positive feelings about themselves and their level of subjective well-being (SWB) despite belonging to a less fortunate economic situation. These results will hopefully encourage Indonesian scholars and researchers to elaborate deeper in future studies. Penelitian ini bertujuan menjelaskan kesejahteraan subjektif (subjective well-being; SWB) anak Indonesia terkait kesejahteraan materi. Indonesia masih dikategorikan sebagai negara berkembang, dan beberapa penelitian terdahulu mengungkapkan korelasi antara status ekonomi dan kesejahteraan subjektif orang dewasa. Namun, studi yang memfokuskan pada kesejahteraan materi anak Indonesia dari perspektif mereka sendiri masih sangat terbatas. Studi ini menggunakan data dari survei Children’s Worlds gelombang ketiga yang dilakukan di Indonesia. Sampel penelitian terdiri dari anak-anak usia 10 tahun dan 12 tahun (N = 14.576; 49,35% laki-laki; 50,65% perempuan). Kesejahteraan subjektif diukur dengan menggunakan dua skala: Children’s Worlds Subjective Well-Being Scale (CW-SWBS) dan Overall Life Satisfaction (OLS) dengan butir pertanyaan tunggal. Kesejahteraan materi diukur berdasarkan dimensi status ekonomi keluarga, kekurangan materi, frekuensi kekhawatiran tentang situasi keuangan keluarga, dan frekuensi ketersediaan makanan untuk dikonsumsi setiap hari. Data kemudian dianalisis dengan menggunakan statistik deskriptif. Teori Cummins tentang kesejahteraan subjektif digunakan untuk menjelaskan temuan. Hasil penelitian menunjukkan bahwa anak-anak dari keluarga dengan status ekonomi tinggi yang tidak melaporkan kekurangan materi, tidak pernah khawatir tentang keuangan keluarga, dan selalu memiliki cukup makanan untuk dikonsumsi setiap hari menunjukkan skor rata-rata kesejahteraan subjektif yang lebih tinggi pada dua skala kesejahteraan subjektif dibandingkan anak-anak dari keluarga dengan status ekonomi menengah dan rendah. Namun, anak-anak dari status ekonomi menengah dan rendah menunjukkan skor kesejahteraan subjektif yang relatif tinggi, yang mengungkapkan bahwa anak-anak dapat menjaga perasaan positif tentang diri mereka sendiri dan tingkat kesejahteraan subjektifnya meskipun tergolong ke dalam status ekonomi yang kurang mapan. Hasil penelitian diharapkan dapat mendorong para ilmwuan dan peneliti di Indonesia untuk lebih mendalami fenomena ini pada studi-studi selanjutnya.